1999
DOI: 10.1007/s004280050346
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial stromal sarcomas: immunohistochemical, electron microscopical and cytogenetic findings in two cases

Abstract: Uterine sarcomas are approximately 3% of all malignant uterine corpus tumours. Of these, the tumours that originate solely in the stromal elements of the uterine wall are infrequent and have not been well characterized cytogenetically. We report two cases of endometrial stromal sarcomas (ESS), one low grade and one high grade, diagnosed by conventional histology, immunocytochemistry, electron microscopy and cytogenetics. Morphologically clear-cut differential structures were seen at optical, immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The lack of a unique immunohistochemical profile for ESS further hampers diagnostic efforts. Cytogenetic studies have not shown consistent chromosomal abnormalities and thus, their utility in the diagnosis of ESS is limited (5,12).…”
mentioning
confidence: 99%
“…The lack of a unique immunohistochemical profile for ESS further hampers diagnostic efforts. Cytogenetic studies have not shown consistent chromosomal abnormalities and thus, their utility in the diagnosis of ESS is limited (5,12).…”
mentioning
confidence: 99%
“…In addition to the 7; 17-translocation, chromosomal band 7 ϳ p21 ] p15 was found rearranged in seven ESS with other partners than chromosome 17 (Laxman et al, 1993;Hrynchak et al, 1994;Iliszko et al, 1998;Gil-Benso et al, 1999;Micci et al, 2003Micci et al, , 2006 suggesting that alternative, pathogenetically equivalent variant translocations exist in this tumor type. Indeed, the first such variant, a t(6; 7), was recently described in two ESS in which a der(7)t(6; 7)(p21;p15)del(6)(q21) and a der(7)(7qter ] 7p15::6?::15?::3?…”
Section: Rearrangements Of Genes Due To Chromosomal Aberrationsmentioning
confidence: 99%
“…The PHF1 gene is located in chromosomal band 6p21, which is the third most commonly rearranged band in ESS, involved as it is in ten of altogether 34 reported tumors and with different translocation partners (Fresia et al, 1992;Laxman et al, 1993;Hrynchak et al, 1994;Fuzesi et al, 1995;Gil-Benso et al, 1999;Sonobe et al, 1999;Micci et al, 2003Micci et al, , 2006. In four cases, it was recombined with chromosomal region 7p ϳ p22 ] p15 and in two of these, the already mentioned JAZF1/PHF1 fusion gene was identified (Micci et al, 2006).…”
Section: Rearrangements Of Genes Due To Chromosomal Aberrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one tumor (Iliszko et al, 1998), there were three different 7p rearrangements, described as der(2)t(2; 7), del(7)(p15p13) and der(7), resulting from an unbalanced t(7; 17). Another tumor with an add(7)(p21) (Gil-Benso et al, 1999) and a case in which both chromosomes 7 were involved in complex rearrangements at 7p15 have been described. The involvement of the same bands 7p21 ϳ p15 in six cases without a t(7; 17) (p21 ϳ p15;q12 ϳ q21), suggests that this region may be pathogenetically involved in ESS tumorigenesis in more than one way.…”
Section: Cytogenetics Of Essmentioning
confidence: 99%